PESAN MORAL DALAM DONGENG KANCIL DAN SAHABAT KARIBNYA KARYA FATIHARIFAH DAN NIA YUSTISIA - Ikha Listyarini; Muhammad Arief Budiman (Jurnal CULTURE (Culture, Language, and Literature Review), 2018)
Each narrative story contains a moral message. The moral message is impliedfrom within the story conveyed by the author. To know the moral message of afairy tale, we must read it over and over again. Tales told since childhood canbuild a better child's morale. Fairy tales are not only heard orally, but it can alsothrough the book, of course a book that contains many moral messages in it. Thetype of research is qualitative with descriptive method. The data in this researchis the moral message and data source of the book of Dongeng Kancil dan SahabatKaribnya by Fatiharifah and Nia Yustisia. Based on the results of data analysisthrough research descriptions, then we found a moral message on the bookDongeng Kancil dan Sahabat Karibnya by Fatiharifah and Nia Yustisia. From theanalysis results obtained percentage of each moral value in the overall fairy talethat is respect 8%, responsible 11%, honesty 3%, fairness 3%, tolerance 6%,wisdom 9%, self discipline 8%, mutual help 17%, care for others 13%, cooperation 6%, courage 6%, and democratic attitude 9%. Moral values areshown through the sentences in each fairy tale. The conclusion of this research isthe existence of moral message contained in the fairy tale on the book DongengKancil dan Sahabat Karibnya by Fatiharifah and Nia Yustisia.Keywords: Moral message, Fairy tale, Moral values, The Kancil,.